CYSTIC ENDOMETRIAL HYPERPLASIA IN A BATCH- A CASE REPORT - P. Biju (Director of Academics and Research, Kerala Veterinary and Animal Sciences University, 1995)
Pathological changes in the uterus of a bitch with cystic endometrial hyperplasia is presented